No longer written : the use of conjectural emendation in the restoration of the text of the New Testament, the Epistle of James as a case study - Wettlaufer, Ryan Donald (New Testament tools, studies and documents., 2013)
Ryan Wettlaufer explores how conjectural emendation can be used in New Testament textual criticsm to restore readings which were once found in the original text but now are No Longer Written.